Deforestation Trends in the Congo Basin : Wood-Based Biomass Energy - Behrendt, Hannah; Megevand, Carole; Sander, Klas (World Bank, Washington, DC, 2016)
Congo Basin countries rely more on wood-based biomass to meet their energy needs than most other countries in the world. Wood fuel production is increasing in Congo Basin countries. Urbanization often produces a shift from fuel wood to charcoal consumption, because charcoal is cheaper and easier to transport and store. Charcoal is produced mostly using traditional techniques, with low transformation efficiencies. Under a business as usual scenario, charcoal supply can represent the single biggest threat to Congo Basin forests in the coming decades. This report aims at providing some thinking on how Congo Basin could meet their energy needs in a forest-friendly manner. It is one of a series of outputs prepared during a two-year exercise to analyze and better understand the deforestation dynamics in the Basin. It presents the main findings related to the wood fuel sector in the Congo Basin and its potential impact on forest cover. It is based on an in-depth analysis of the sector (past trends and future prospects). It also builds on results derived from a modeling exercise conducted by the International Institute for Applied Systems Analysis (IIASA) that examined the national and regional trends in in wood-based biomass energy use and the impacts on Congo Basin forests. The report is structured as follows: chapter one gives an overview of the wood fuel sector in the six Congo Basin countries, including an analysis of its impact so far on forest cover; chapter two presents the prospects of energy needs and production in the near future, and the potential impacts on forest under a business as usual scenario; and chapter three identifies potential key levers in the wood fuel sector that could limit adverse impacts on forest cover.